The Invisible Web (Intermediate level) - Lehmann, Susan; Schultz, Norah (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
a vast amount of information is available to students today. The internet and basic search engines, or even meta search engines, are just the top layer and often are not the best for academic work. In this exercise, students learn to navigate more research-oriented tools.